Midnight salvage : poems, 1995-1998 - Rich, Adrienne Cecile (New York : Norton, 1999)
In these risky new poems, Rich dares to look and to extend her poetic language as witness to the treasures--the midnight salvage--rescued from fear and violence. Andrienne Rich's work has long challenged social plausibilities built on violence & demoralizing power. The poems in Midnight Salvage are risky, infused with the cruelty of history, the presence of the body, the beauty of the natural world, with human love & longing
Art of translation -- For an anniversary -- Midnight salvage -- Char -- Modotti -- Shattered head -- 1941 -- Letters to a young poet -- Camino real -- Plaza Street and Flatbush -- Seven skins -- "The night has a thousand eyes" -- Rusted legacy -- Long conversation
Keywords: American poetry -- 20th century